2019
DOI: 10.1037/emo0000513
|View full text |Cite
|
Sign up to set email alerts
|

You look pretty happy: Attractiveness moderates emotion perception.

Abstract: A happy face advantage has consistently been shown in emotion categorization tasks; happy faces are categorized as happy faster than angry faces as angry. Furthermore, social category cues, such as facial sex and race, moderate the happy face advantage in evaluatively congruent ways with a larger happy face advantage for more positively evaluated faces. We investigated whether attractiveness, a facial attribute unrelated to more defined social categories, would moderate the happy face advantage consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…The most interesting findings concern the stereotype of black men and women as being more angry or hostile, as compared to whites of the same gender. As discussed in related work [19], the faces of non-white individuals tend to be categorized easier as being angry when they show an angry emotion compared to whites. We confirmed empirically that some EAS (in particular, Amazon and Microsoft) were more likely to correctly infer an angry expression on a black man versus a white man.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The most interesting findings concern the stereotype of black men and women as being more angry or hostile, as compared to whites of the same gender. As discussed in related work [19], the faces of non-white individuals tend to be categorized easier as being angry when they show an angry emotion compared to whites. We confirmed empirically that some EAS (in particular, Amazon and Microsoft) were more likely to correctly infer an angry expression on a black man versus a white man.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, in the same study, Korean participants perceived neutral Caucasian faces as being negative. In another study, Hugenberg et al provided evidence of a prevalent cultural stereotype that African Americans are aggressive [15,19]. They extended this research by hypothesizing that the racial prejudice is strongly associated with hostile emotions and demonstrated that there is a tendency to categorize the emotionally ambiguous faces of African Americans under emotions of hostility (e.g., anger) [16].…”
Section: Social Stereotyping and Potential Harmmentioning
confidence: 96%
See 1 more Smart Citation
“…Facial attractiveness not only affects social interactions but also modulates emotional perception and may directly impact emotional experience 22,23 . Nevertheless, there is insufficient evidence to expound on the relationship between makeup and emotional contagion.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we hypothesize the effect of makeup on emotions may be unbalanced. Evidence from related studies has indicated an asymmetrical mutual influence of different emotional expressions and facial attractiveness 22,31,32 , which suggests that wearing makeup may only affect positive or negative emotional contagion. Moreover, for neutral expressions,…”
Section: Introductionmentioning
confidence: 99%